Knowledge Gaps in Circular Product Development: A Systematic Literature Review of the Manufacturing Industry - Twardzik, Jan Luca; Humpert, Lynn; Cichon, Gerrit; Dumitrescu, Roman (Lecture Notes in Mechanical Engineering)

Knowledge Gaps in Circular Product Development: A Systematic Literature Review of the Manufacturing Industry - Twardzik, Jan Luca; Humpert, Lynn; Cichon, Gerrit; Dumitrescu, Roman (Lecture Notes in Mechanical Engineering)

Creep Effects of Thermoplastic Flange Systems - Bartmann, Finn; Riedl, Alexander; Moritzer, Elmar (Lecture Notes in Mechanical Engineering)

Systematic AI Potential Analysis for Sustainable Rough Factory Planning - Kürpick, Dominik; Disselkamp, Jan-Philipp; Lick, Jonas; Hovemann, Aschot; Dumitrescu, Roman (Lecture Notes in Mechanical Engineering)
Abstract Current megatrends are influencing industrial production and leading to ever shorter innovation cycles. The resulting fast pace of production requirements requires an accelerated development of production systems and an associated increase in efficiency in factory planning. Due to its knowledge-intensive activities, rough factory planning promises great potential to be supported in its activities by innovative technologies such as artificial intelligence. However, industrial companies face the challenge to recognize the potential of artificial intelligence (AI) in rough planning and to evaluate possible applications in their business context. As a result, a systematic approach for analyzing AI potential in rough factory planning was developed as part of this work. The system includes a procedural model and several artefacts used in it, which support the identification and evaluation of AI potential in organizations. This approach not only streamlines the planning process but also aligns with sustainable manufacturing principles by enhancing resource efficiency, promoting intelligent system design, and fostering innovation in product development and manufacturing processes.

Soft Sensor Model of Phase Transformation During Flow Forming of Metastable Austenitic Steel AISI 304L - Rozo Vasquez, Julian; Kersting, Lukas; Arian, Bahman; Homberg, Werner; Trächtler, Ansgar; Walther, Frank (Lecture Notes in Mechanical Engineering)
This paper deals with the modeling of a soft sensor for detecting α’-martensite evolution from the micromagnetic signals that are measured during the reverse flow forming of metastable AISI 304L austenitic steel. This model can be prospectively used inside a closed-loop property-controlled flow forming process. To achieve this, optimization by means of a non-linear regression of experimental data was carried out. To collect the experimental data, specimens were produced by flow forming seamless tubes at room temperature. Using a combination of production parameters (like the infeed depth and feed rate), specimens with different α’-martensite contents and wall-thickness reductions were produced. An equation to compute α’-martensite from both specific production-process parameters and micromagnetic Barkhausen noise (MBN) measurements was obtained using numerical methods. In this process, the behavior of the quantity of interest (namely, the α’-martensite content) was mathematically evaluated with respect to non-destructive MBN data and the feed rate that was used to produce the components. A combination of exponential and potential functions was defined as the ansatz functions of the model. The obtained model was validated online and offline during the real flow forming of workpieces, obtaining average deviations of up to 7% α’-martensite with respect to the model. The implementation of the soft sensor model for property-controlled production represents an important milestone for producing high-added-value components on the basis of a well-understood process-microstructure-property relationship.

Analysis and Modelling of the Deformation in the Manufacture of Flange-Contours by the Combined Friction-Spinning and Flow-Forming Process - Dahms, Frederik; Homberg, Werner (Lecture Notes in Mechanical Engineering)

Modeling and Parameterization for a 3D Simulation of Clinching with an Extensible Die - Rossel, M.; Meschut, G. (Lecture Notes in Mechanical Engineering)

Numerical Approach to Model a Novel Electrohydraulic Incremental Forming Process for the Manufacture of Pillow Plate Heat Exchangers - Holzmüller, Maik; Gong, Yi; Bader, Fabian; Henke, Armin; Homberg, Werner (Lecture Notes in Mechanical Engineering)

Numerical Investigation of the Coupled Friction Behavior in the Clinching Process Chain - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Lecture Notes in Mechanical Engineering)

Friction-Induced Recycled Aluminium Semi-finished Products in Thermo-mechanical Joining Technology - Borgert, Thomas; Homberg, Werner (Lecture Notes in Mechanical Engineering)
Due to current global challenges regarding energy security as well as climate change the importance of preserving the nature and all available resources is steadily increasing. In order to achieve the energy-saving and climate targets, it is not only necessary to develop new processes and processing possibilities, but also to optimise known process chains with regard to energy and resource efficiency in the area of production technology. Here, the recycling of supposed production waste represents an opportunity to save energy. In addition to the conventional and smelting metallurgical recycling process, extensive research activities have therefore been carried out for alternative solid-state recycling processes. One example is the friction-induced recycling process, which has been used in past studies to demonstrate the energy- and resource-efficient production of semi-finished products from aluminium scrap such as chips. In addition, properties like chemical composition and strength can be adjusted locally and in terms of processing time. This can be used to improve the versatility of further processing steps.

Influence of Shell Material on the Microstructure and Mechanical Properties of Twin-Roll Cast Al-Si-Mg Alloy - Grydin, Olexandr; Neuser, Moritz; Schaper, Mirko (Conference: ICTP 2023: Proceedings of the 14th International Conference on the Technology of Plasticity - Current Trends in the Technology of PlasticityAt: Cannes (France))

Experimental and Numerical Investigation of Clinched Joints Under Shear Tensile Loading at High Strain Rates - Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Lecture Notes in Mechanical Engineering)

Model-Based Investigation of the Influence of Wheel Suspension Characteristics on Tire Wear - Schütte, Jan; Sextro, Walter (Lecture Notes in Mechanical Engineering)

The Paradigm of Self-optimization - Dellnitz, Michael; Dumitrescu, Roman; Flaßkamp, Kathrin; Gausemeier, Jürgen; Hartmann, Philip; Iwanek, Peter; Korf, Sebastian; Krüger, Martin; Ober-Blöbaum, Sina; Porrmann, Mario; Priesterjahn, Claudia; Stahl, Katharina; et al. (Lecture Notes in Mechanical Engineering)

Methods for the Design and Development - Anacker, Harald; Dellnitz, Michael; Flaßkamp, Kathrin; Groesbrink, Stefan; Hartmann, Philip; Heinzemann, Christian; Horenkamp, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Korf, Sebastian; Krüger, Martin; Müller, Wolfgang; et al. (Lecture Notes in Mechanical Engineering)